1983
DOI: 10.1042/bj2150303
|View full text |Cite
|
Sign up to set email alerts
|

The optical properties of CuA in bovine cytochrome c oxidase determined by low-temperature magnetic-circular-dichroism spectroscopy

Abstract: The visible-near-i.r.-region m.c.d. (magnetic-circular-dichroism) spectrum recorded at low temperature in the range 450-900 nm is reported for oxidized resting mammalian cytochrome c oxidase. M.c.d. magnetization curves determined at different wavelengths reveal the presence of two paramagnetic species. Curves at 576, 613 and 640 nm fit well to those expected for an x,y-polarized haem transition with g values of 3.03, 2.21 and 1.45, i.e. cytochrome a3+. The m.c.d. features at 515, 785 and 817 nm magnetize as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 38 publications
(58 reference statements)
4
38
0
Order By: Relevance
“…In our model the centre labelled A is shown to be clearly similar in structure to Cu, in bovine cytochrome c oxidase [15,16]. Although the form of A is controversial, the 7-line hyperfine structure in the EPR spectrum of this centre has found an explanation so far only in terms of a binuclear mixed-valence metal dimer 161.…”
Section: Resultsmentioning
confidence: 75%
“…In our model the centre labelled A is shown to be clearly similar in structure to Cu, in bovine cytochrome c oxidase [15,16]. Although the form of A is controversial, the 7-line hyperfine structure in the EPR spectrum of this centre has found an explanation so far only in terms of a binuclear mixed-valence metal dimer 161.…”
Section: Resultsmentioning
confidence: 75%
“…2 A) has a spectrum distinct from that of Cu A in the two earlier phases (data not shown), and must therefore be ascribed to other processes (see below). It has indeed been demonstrated that the near-infrared absorbance at 820 nm cannot be completely ascribed to Cu A (27).…”
Section: Resultsmentioning
confidence: 99%
“…3 of the MCD spectra at 4.2 K of the R denitr$icans Cu, domain, the Cu, centre deconvoluted from the MCD spectrum of bovine heart cytochrome-c oxidase (Greenwood et al, 1983), and that of the mutant form of nitrous-oxide reductase (N,ORV). The spectrum of Cu, in bovine heart cytochrome-c oxidase has been obtained by two independent methods, namely by difference spectroscopy between different ligated forms using the magnetisation characteristics (field and temperature dependence) of each feature as a guide to its assignment (Greenwood et al, 1983), and from the MCD of an orientated sample (Greenwood et al, 1988). The Tn5 mutant form of nitrous-oxide reductase is deficient in copper, containing up to two copper atomddimer instead of the eight found in the wild-type enzyme and has been shown to contain only the Cu, centre (Viebrock and Zumft, 1987;Dooley et al, 1991 ;Antholine et al, 1992).…”
Section: Resultsmentioning
confidence: 99%